Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/adma.202200705
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth Regulation of 2D/3D Perovskite Films for Solar Cells with Both High Efficiency and Stability

Abstract: 2D perovskites, such as 2D Ruddlesden-Popper (RP) and 2D Dion-Jacobson (DJ) perovskites, have attracted much attention owning to their better structure and environmental stability compared with their 3D analogs. [12][13][14][15][16] However, the efficiencies of 2D PSCs are still much lower than that of state-of-theart 3D PSCs. One strategy to combine the advantages of the high stability of 2D perovskite and high efficiency of 3D perovskite is developing the 2D/3D hybrid perovskites by embedding a highly stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 52 publications
2
112
0
Order By: Relevance
“…It has been widely reported that the incorporation of 2D perovskites in PVSCs could enhance device stability due to their excellent intrinsic stability. [35,[43][44][45] Therefore, we further measured the thermostability and photostability of PVSC based on 3D/2D heterostructure and control device. [18,21,22] As shown in Figure 4a,b, the evolution of PCE, V OC , FF, and J SC over 1000 h was recorded for the control and 3D/2D devices under 65 °C in nitrogen atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely reported that the incorporation of 2D perovskites in PVSCs could enhance device stability due to their excellent intrinsic stability. [35,[43][44][45] Therefore, we further measured the thermostability and photostability of PVSC based on 3D/2D heterostructure and control device. [18,21,22] As shown in Figure 4a,b, the evolution of PCE, V OC , FF, and J SC over 1000 h was recorded for the control and 3D/2D devices under 65 °C in nitrogen atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…The curve of V OC with light intensity has been widely used to investigate non-recombination in perovskite solar cells. 48,49 The value of the slope reflects the non-recombination according to eqn (3): 50,51…”
Section: Resultsmentioning
confidence: 99%
“…The curve of V OC with light intensity has been widely used to investigate non-recombination in perovskite solar cells. 48,49 The value of the slope reflects the non-recombination according to eqn (3): 50,51 where k B is the Boltzmann constant, n is the ideality factor, and T is the thermodynamic temperature. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The long-term stability of small-area Pero-SCs has reached about one year, far below 25 years of silicon cells [68]. To date, a series of strategies have been adopted to improve the device stability, such as grain boundary passivation [69], interface/stress engineering [70][71][72][73], low dimension structure [68,74,75], and device encapsulation [76]. Here, the degradation of PPMs will be highlighted to analyze the module stability issue with the relative scribes.…”
Section: Stability Of Ppmsmentioning
confidence: 99%